2012
DOI: 10.1371/journal.pone.0032584
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Autophagy Prevents Bortezomib-Induced NF-κB Activation by Reducing I-κBα Degradation in Lymphoma Cells

Abstract: Here we show that bortezomib induces effective proteasome inhibition and accumulation of poly-ubiquitinated proteins in diffuse large B-cell lymphoma (DLBCL) cells. This leads to induction of endoplasmic reticulum (ER) stress as demonstrated by accumulation of the protein CHOP, as well as autophagy, as demonstrated by accumulation of LC3-II proteins. Our data suggest that recruitment of both ubiquitinated proteins and LC3-II by p62 directs ubiquitinated proteins, including I-κBα, to the autophagosome. Degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 43 publications
6
79
0
Order By: Relevance
“…16,19,[24][25][26][27][28][29] Our results demonstrate the feasibility of this approach, as well as intracellular accumulation of AVs during combined stimulation of the autophagy pathway and inhibition of its final step.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…16,19,[24][25][26][27][28][29] Our results demonstrate the feasibility of this approach, as well as intracellular accumulation of AVs during combined stimulation of the autophagy pathway and inhibition of its final step.…”
Section: Discussionmentioning
confidence: 72%
“…Autophagy inhibition augments the efficacy of many anticancer therapies in cell lines and animal models. [23][24][25][26][27] Specifically, preclinical evidence suggests that autophagy inhibition synergistically increases bortezomib cytotoxicity in laboratory models of myeloma, [28][29][30] colon carcinoma, 31 and hepatocellular carcinoma.…”
Section: Combined Autophagy and Proteasome Inhibitionmentioning
confidence: 99%
“…Furthermore, the relapse of multiple myeloma tumors observed in patients is correlated with higher levels of NFkB (17). It has also been shown that bortezomib induces I-kBa degradation, which is removed by the autophagic process, and activates NFkB transcriptional activity (18). These and other results suggest that NFkB is a key target of bortezomib.…”
Section: Introductionmentioning
confidence: 74%
“…2H). [30][31][32][33][34][35] However, this often occurs under stressful conditions such as nutrient starvation, extracellular matrix (ECM) detachment, HSP90 inhibition, proteasome inhibition, infections, and treatment with chemotherapy drugs. 20,[23][24][25][26][27]29,[31][32][33]35 Therefore, the ability of autophagy to degrade signaling proteins under basal growth conditions and thereby to ensure tumor-suppressive functions remains to be established.…”
mentioning
confidence: 99%
“…2H). [27][28][29][30]32,33,35 Importantly, upon inhibition of autophagy by chloroquine treatment, we identified that RHOA is ubiquitinated and recognized by the autophagy receptor SQSTM1. 17 We therefore propose that RHOA, once activated, undergoes ubiquitination, recruiting the scaffold protein SQSTM1 that bridges RHOA to the autophagosome marker LC3 for selective autophagic targeting.…”
mentioning
confidence: 99%